Cocoa - wonders for chocolate lovers - Selamat, Jinap (Universiti Putra Malaysia Press, 2004)
The components of cocoa attribute to the unique of flavor, texture, color characteristics and health benefits of chocolate. Cocoa flavor is very specific; therefore it cannot be replaced by sources other than cocoa. It consists of cocoa aroma which comprises volatile compounds produced through Maillard reaction and taste, a balanced combination of bitterness, sourness and sweetness derived form non-volatile compounds, such as phenols, acids and peptides, respectively. Proper handling and processing would prevent the development of undesirable properties of cocoa such as astringency, moldy, hammy, smoky and excessive sourness. Cocoa butter contributes to the unique texture of chocolate, which gives the smoothness and glossy appearance, and melts only at body temperature. The natural color of chocolate comes only from cocoa; color of cocoa can be of different shades to reflect the uniqueness of the food it contained. Genetic and origin, fermentation, drying, roasting, alkalizations, refining and conching are the main factors which influence the flavor, texture and color of cocoa and its characteristics in chocolate. Recently, cocoa and chocolate have become the objects of increased scientific research mainly because or their phytochemical composition. Cocoa is rich in polyphenol (10 – 18%) which had anti-oxidant activities, responsible for the prevention of many diseases and possible anti-cariogenic effects. Stearic acid in cocoa butter, although saturated, is neutral with respect to blood and suppresses the effect of cholesterol. Cocoa contains phenylethylalanine, which strikes the endocrine gland to secrete hormone associated with happy feeling. Research and development initiatives in the area include flavor improvement using enzymes, detection and quantification of fats other than cocoa butter, the production of polyphenol fractions, cocoa flavor from other plant proteins, fat-free cocoa powder and heat-resistant chocolates.